A Little Rosewood Casket - Chaulk, Elizabeth M. (1987)
Sentimental song in which a dying girl laments to her family (mother and brother) the loss of her lover to another and entrusts her baby to her family's care. Ends with a warning to other girls to avoid her fate. "Old-timey" parlour song. Recorded by original Carter Family. Sentimental "tear-jerker". Belden, 220 (4); Family Herald, 14/9/21; 20/10/26; 23/2/27; 5/2/36; 27/7/38; 15/7/42; 5/1/44; 22/11/51. The delivery of the baby to the girls mother and the final warning do not appear as frequently as the rest of the song.